Feeling younger in rural Burkina Faso: exploring the role of subjective age in the light of previous research from high-income countries - Schönstein, Anton; Ngo, Dinh Thao Trinh; Stephan, Yannick; Siè, Ali; Harling, Guy; Bärnighausen, Till; Wahl, Hans-Werner (The journals of gerontology. Series B, Psychological sciences, social sciences, 2021)
Previous research on subjective age (SA), that is, how young or old a person feels relative to their chronological age, has shown that older adults tend to feel younger than they are (by about 15%-20%), but the extent of this effect depends, in part, on their health. However, as most of the studies have been conducted in Western countries, it is unclear how well these results generalize to culturally different samples. Objectives, therefore, were to examine SA in middle-aged and older adults from a very low-income setting in rural Burkina Faso, to examine associations between SA and health/quality of life-related measures, and to compare findings with Western studies.Representative, cross-sectional sample of N = 3,028 adults (≥40 years, recruited in 2018) from north-western Burkina Faso. Data included questionnaires on depression (Patient Health Questionnaire-9) and quality of life (World Health Organization Quality of Life scale, including subjective health) as well as performance-based and objective health-related measures (Community Screening Instrument for Dementia as cognitive screening, walking speed).Respondents felt on average 3% younger (SD = 0.13) than their chronological age, with 48% (95% confidence interval: 0.46-0.50) feeling younger—27 percentage points lower than seen in representative Western studies. Lower depression, better walking speed, cognition, and quality of life were all associated with younger SA.Middle-aged and older adults in Nouna felt less young than similar age groups in Western studies. One of the reasons may be that youthfulness is less of a value outside Western cultures. As in Western studies, parts of the variation in SA can be explained by health parameters.
Gesehen am 05.01.2022